P257 Multiple clinical manifestations of catecholamine secreting paraganglioma. (17th January 2020) - Garibaldi, S; Suma, S; Coli, S; Buratti, S; Gaibazzi, N
Abstract: A 37 years old woman was referred to our hospital due to the onset since the previous day of vertigo associated with nausea and headache. Her previous history revealed an hospitalization ten years before for Tako Tsubo Cardiomyopathy, during which the diagnosis of left temporo-jugular catecholamine secreting paraganglioma was made. Subsequently, there were several hospitalizations for multiple cardiac manifestations, such as acute coronary syndrome during hypertensive crisis, acute pulmonary oedema, one relapse for TakoTsubo syndrome and then an episode of torsade de pointes (TdP) during hypokalemia and elongated QT. The surgical removal of the mass was always rejected by the patient, and therefore, only radiotherapy was performed with significant reduction of the tumour dimensions. Moreover, alpha and beta adrenergic blockers were always administrated. At the admission, she complained neurological symptoms, in particular balance disorder and dysmetria. Brain Computed tomography (CT) was performed and it showed left posterior cerebellar infarction in late acute clinical phase, without haemorrhage. The patient underwent angiography that excluded cerebral artery dissection but showed acute occlusion of posterior internal cerebral artery. Echocardiogram showed moderate left ventricular hypertrophy with normal global and segmental kinetics, left atrial dilatation; besides, left ventricular apical thrombus was excluded. Holter ECG monitoring showed very frequent polymorphic ventricular and supraventricular extrasystolic beats. Urinary metanephrines were markedly increased. In particular urinary normetanephrine was up to 9 times the upper limit of normality (4874 ug/L, normal range 162-527 ug/24 h). Since the surgical intervention was always refused, this case is a rare documentation of the several different cardiovascular clinical manifestation due to catecholamine secretion in a single patient. Paraganglioma could be a catecholamine secreting tumour that arises from cromaffin tissue of the sympathetic nervous system. Clinical manifestations of paraganglioma are extremely variable leading to its designation as "great mimic". Adrenal tumours are associated with several cardiovascular diseases including LV hypertrophy, myocardial infarction, cardiac arrhythmias, heart failure and Tako Tsubo cardiomyopathy. Cerebral accident is a rare manifestation of adrenergic crisis with several possible aetiologies such as vasospasm or cardioembolic events. In our clinical case, considering the type and localization of the cerebral ischemic injury, the stroke is likely to have a cardioembolic etiology. Apical left ventricular trombus and PFO were excluded. Therefore, in view of left atrial enlargement and the frequent supraventricular ectopy, even in the absence of documented arrhythmia, an undiagnosed episode of catecholamines induced atrial fibrillation was suspected, with subsequent cardioembolic event.